Comparison of anesthetic and analgesic effect of isobaric 0.5% ropivacaine versus levobupivacaine with fentanyl as adjuvant in lower limb surgeries under spinal anesthesia- a randomized double-blind, interventional study - Sampat Rathod; Chetali Das; Trishala Jain (Journal of Applied Pharmaceutical Research, 2023)
Background: Spinal anesthesia is a widely used technique for lower abdomen and lower limb surgeries. We used opioids as an adjuvant to attain a dense block and increase the duration of surgery. The purpose of the study is to compare the anesthetic and analgesic effects of intrathecal isobaric 0.5% ropivacaine-fentanyl versus isobaric 0.5% levobupivacaine-fentanyl in patients undergoing lower limb surgeries. Material and methods: This prospective randomized double-blind interventional study was carried out in ASA I and II, aged 18 to 60 years. Injection Isobaric ropivacaine (0.5%) 2.5 ml with injection fentanyl 0.5 ml (25 μg) intrathecally in group A (n=30) and Inj. Isobaric levobupivacaine isobaric (0.5%) 2.5 ml with injection fentanyl 0.5 ml (25 μg) intrathecally in group B (n=30) was used. The sealed envelope method was used for group allocation. Results: Both groups' demographic and hemodynamic data were comparable. There was a faster onset of sensory and motor block in the levobupivacaine group than in the ropivacaine group with fentanyl, and the result was statistically significant. (P value <0.001). Two-segment regression mean time was statistically significant between groups (P value > 0.008). Sensory and motor block durations were shorter in the ropivacaine than in the levobupivacaine with the fentanyl group. There is a statistically significant difference between the two groups' time to first-dose rescue analgesia. Conclusion: We deduce in our study that using intrathecal 2.5 ml of 0.5% ropivacaine with 0.5ml fentanyl (25 micrograms) helps in early ambulation and can be used in day-care lower limb surgeries when compared with levobupivacaine.